Licensing Complementary Patents: 'Patent Trolls', Market Structure, and 'Excessive' Royalties - Anne Layne-Farrar; Klaus M. Schmidt (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2009)
The infamous Blackberry case brought new attention to so-called 'patent trolls' and began the general association of trolls with 'non-practicing' patent holders. This has had important legal consequences: Namely, patent holders have been denied injunctive relief because they did not practice the patents themselves. In this paper we analyze how patent holders '- both non-practicing and vertically integrated '- choose their royalties depending on the structure of the upstream and downstream markets and the types of licensing agreements available. We show that a vertically integrated firm has an incentive to raise its rivals' costs and to restrict entry on the downstream market; incentives that do not hold for non-integrated patent holders. An automatic presumption that a non-integrated patent holder will charge higher royalties than a vertically integrated company is therefore unfounded. Whether a company charges 'excessive' royalties depends on whether there is scope for hold-up, either because of sunk investments on the part of potential licensees or because of 'weak' patents held by the licensor. These factors are orthogonal to whether patent holders are practicing or not
urn:nbn:de:bvb:19-epub-13278-3
Keywords: 330